2019
DOI: 10.3389/fmicb.2018.03222
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl Disulfide From Garlic Oil Inhibits Pseudomonas aeruginosa Quorum Sensing Systems and Corresponding Virulence Factors

Abstract: Previously, we determined that diallyl disulfide (DADS) from garlic oil can inhibit Pseudomonas aeruginosa PAO1 pathogenic factors by inactivating the transcription of key genes from three quorum sensing (QS) systems (las, rhl, and pqs) based on the effects of DADS on growth, virulence factor production (elastase, pyocyanin, biofilm, and swarming motility), and RNA transcription (real-time q-PCR). To further investigate the mechanisms underlying the inhibition of the three P. aeruginosa QS systems by DADS, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…The antimicrobial effects of DATS or other diallyl sulfide derivatives have not been studied in C. jejuni before. On the other hand, several studies have been conducted on investigating the antimicrobial effect of DAS, DADS, DAT, DATS on P. aeruginosa ; DATS showed an equal antimicrobial effect to the multidrug-resistant P. aeruginosa as the garlic essential oil, and both were stronger compared to DAS, DADS and DAT according to the MIC results [ 19 , 21 ]. A previous study treated P. aeruginosa by 2.84 mg/L for 120 h and observed a 50% decrease of cell density by the hemocytometer counting method, while the inhibition efficiency was increased with the increasing of treatment dose [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial effects of DATS or other diallyl sulfide derivatives have not been studied in C. jejuni before. On the other hand, several studies have been conducted on investigating the antimicrobial effect of DAS, DADS, DAT, DATS on P. aeruginosa ; DATS showed an equal antimicrobial effect to the multidrug-resistant P. aeruginosa as the garlic essential oil, and both were stronger compared to DAS, DADS and DAT according to the MIC results [ 19 , 21 ]. A previous study treated P. aeruginosa by 2.84 mg/L for 120 h and observed a 50% decrease of cell density by the hemocytometer counting method, while the inhibition efficiency was increased with the increasing of treatment dose [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the sulfides from virulence genes could regulate the quorum sensing (QS) signal molecules and extracellular virulence factors of Pseudomonas aeruginosa both in vivo and in vitro [ 18 ]. Further studies also proved that DADS could inhibit the expression of las , rhl and pqs for QS autoinducer synthesis [ 19 ]. In addition, diallyl sulfide derivatives from garlic also proved to inhibit the QS transcriptional regulators LuxR and LasR [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that four diallyl sulfides (DAS, DADS, DATS, and DATTS) in garlic can inhibit LuxR QS monitoring system (Persson et al ., 2005). In our previous study, we found that DADS from garlic inhibited the gene expression of the QS systems and related virulence genes of the PAO1 strain (Li et al ., 2019). The difference between DADS and DAS is that DADS inhibited the transcription of all the key genes in the three QS systems, while DAS did not inhibit lasI and pqsH .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to DAS, DADS inhibited key genes in the three QS systems of the PAO1 strain (Li et al ., 2018, 2019). One difference between DAS and DADS is that DADS inhibits the transcriptions of all key genes in the three QS systems of the PAO1 strain, including lasI and pqsH , whereas DAS does not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation